'Hopelessly devoted to you': An examination of Winnicott's concept of primary maternal preoccupation in the identity and practice of male group analysts. (June 2018) - McBride, Stephen
The rationale for this study is to explore whether or not the Winnicottian concept of primary maternal preoccupation fits into the identities and features in what male group analysts reflect on and resonate with upon 'giving birth to' and conducting a group. A qualitative, individual case-study approach was employed to attempt to discover and understand how male group analysts make sense of Winnicott's fundamental concept. Wondering and thinking about how a male group analyst 'holds' both the maternal and paternal function in a group is also being thought about to ascertain the impact of these features on clinical practice. Exploring the concept of primary maternal preoccupation lends towards a strong focus on the relationship between mother and baby, mirrored in and seen as a metaphor for the relationship between the group analyst and the group members. Doron argues that in disclosing her depth of feeling towards the changing group membership in the group she was conducting, she identified strongly with the state of primary maternal preoccupation. This study will explore the range of feelings associated with the primary maternal preoccupation male group analysts associate with. Three qualified group analysts with five years' minimum post-qualification experience, with whom there were no boundary issues, were interviewed in a semi-structured interview format to ascertain and develop this understanding. A phenomenological research method was chosen to analyse the collated data from the three individual interviews. Following completion of the three interviews, the participants' texts were analysed resulting in five overall themes being developed. Potential wider scopes and application of the question, potential clinical implications of the topic under discussion and the potential for developing a theoretical discussion in group analysis on what might be coined 'paternal preoccupation' were illuminated and discussed.